Multilevel Logistic regression results of individual and community level factors associated with ANC4+ and ANC8 + service utilization among women aged 15- 49 years in urban Ethiopia from pooled 2000-2019 EDHS data by socioeconomic and demographic subgroups, EDHS 2000- to 2019. - Worku Dechassa Heyi (22676316) (2025)
Multilevel Logistic regression results of individual and community level factors associated with ANC4+ and ANC8 + service utilization among women aged 15- 49 years in urban Ethiopia from pooled 2000-2019 EDHS data by socioeconomic and demographic subgroups, EDHS 2000- to 2019.